Molecular detection of methicillin-resistant Staphylococcus aureus (MRSA) in ornamental birds having public health significance (Journal of the Bangladesh Agricultural University, 2020)
There has been an increase in the demand for ornamental birds as pets in Bangladesh. However, issues of Antimicrobial Resistance (AMR) in ornamental birds remain poorly understood. Methicillin-resistant Staphylococcus aureus (MRSA) are major human health problem. Present studywas designed to investigate the potentiality of ornamental birds as a source for MRSA that could transmit to human. A total of 70 samples were collected randomly from various ornamental birds and bird handlers working in the shops. A semi-structured questionnaire-based interview was also conducted with bird shop attendants to suspect the possible AMR origin and transmission. Isolation and identification of MRSA were based on culture, disk diffusion method followed by PCR. Hemolytic activities were tested on blood agar plates Among the 70 samples, 40 (57.14%) were found positive for S. aureus. Phenotypically 77.50% S. aureus were found resistant to oxacillin (methicillin), while by PCR, only ten (25%) isolates were found positive for mecA gene. Both the ornamental birds and bird handlers carried MRSA. Among the MRSA isolates, phenotypically six isolates were found resistant to vancomycin e.g.,VRSA (vancomycin-resistant Staphylococcus aureus).As far we know, this is the first report in Bangladesh describing molecular detection of MRSA from ornamental birds and bird handlers. From this study it is evident that ornamental bird carries MRSA that could transmit to human.J Bangladesh Agril Univ 18(2): 415–420, 2020https://doi.org/10.5455/JBAU.80165